Multicentre randomised controlled trial to evaluate the efficacy of pre-emptive inferior mesenteric artery embolisation during endovascular aortic aneurysm repair on aneurysm sac change: protocol of Clarify IMA study. Issue 2 (16th February 2020) - Ichihashi, Shigeo; Takahara, Mitsuyoshi; Fujimura, Naoki; Nagatomi, Satoru; Iwakoshi, Shinichi; Bolstad, Francesco; Kichikawa, Kimihiko
Abstract : Introduction: Type II endoleak (EL) is frequently seen after endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA) and is often considered responsible for aneurysm sac enlargement if it persists. In order to reduce type II EL and consequent sac enlargement, pre-emptive embolisation of the inferior mesenteric artery (IMA), which is a main source for persistent type II EL, has been introduced in many vascular centres. At present, there is a lack of robust evidence to support the efficacy of pre-emptive embolisation of IMA on reduction of persistent type II EL with subsequent sac shrinkage. Method and analysis: This multicentre, randomised controlled trial will recruit 200 patients who have fusiform AAA ≥50 mm/rapidly enlarging fusiform AAA, with patent IMA, and randomly allocate them either to a pre-emptive IMA embolisation group or non-embolisation control group in a ratio of 1:1. The primary endpoint is the difference of aneurysm sac volume change assessed by CT scans between the pre-emptive IMA embolisation group and the control group at 12 months after EVAR. The secondary endpoints are defined as change of aneurysm sac volume in both groups at 6 and 24 months, freedom from sac enlargement at 12 and 24 months after EVAR, prevalence of type II EL at 1, 6, 12 and 24 months evaluated by contrast-enhanced CT, reintervention rate, aneurysm related mortality, overall survival, perioperative morbidity, volume of contrast media used during EVAR and dosage of radiation. Ethics and dissemination: The protocol has been reviewed and approved by the ethics committee of Nara Medical University (No. 2113). The findings of this study will be communicated to healthcare professionals, participants and the public through peer-reviewed publications, scientific conferences and the University Hospital Medical Information Network Clinical Trials Registry home page. Trial registration number: UMIN000035502.